Configuration Origin Variants of Superior Thyroid, Lingual and Facial Arteries: A Proposal Updating of Current Classification - Fabrizio Zaccheo; Giulia Petroni; Alessandro Guttadauro; Alfredo Passaretti; Maria Elisabetta Campogrande; Gianluca Tenore; Ahmed Mohsen; Andrea Cicconetti (Applied Sciences, 2023)
Background: The aim of this study was to identify variations in the origins of the anterior branches of the external carotid artery (ECA) and to propose an update of the current classification. Methods: The study included 100 carotids arteries from fifty human donors. Classification of anterior branches of external carotid artery was performed according to Vaz’quez et al. (2009). Results: The configuration origins of anterior branches were found as follows: Type I, 82%; Type II, 1%; Type III, 16%. No Type IV was observed. The study identified seven subgroups of anterior branch variations in the external carotid artery. The most frequently observed variations were Subtype Ia in 40% (n = 20) of cases on the right side and Subtype Ib in 38% (n = 19) on the left side. In addition, a rare and previously unclassified configuration was observed in a 72-year-old male donor, where the carotid artery was pentafurcated on the left side. Conclusions: In conclusion, the presence of anatomical variants not previously included in the anterior external carotid artery branching classifications supports the consideration of a revision to the present classification system.